Toward Improving Medication Adherence: The Suppression of Bitter Taste in Edible Taste Films - Silvy Cherian; Brian Sang Lee; Robin M. Tucker; Kevin Lee; Gregory Smutzer (Advances in Pharmacological Sciences)
Bitter taste is aversive to humans, and many oral medications exhibit a bitter taste. Bitter taste can be suppressed by the use of inhibitors or by masking agents such as sucralose. Another approach is to encapsulate bitter tasting compounds in order to delay their release. This delayed release can permit the prior release of bitter masking agents. Suppression of bitter taste was accomplished by encapsulating a bitter taste stimulus in erodible stearic acid microspheres, and embedding these 5 µmeter diameter microspheres in pullulan films that contain sucralose and peppermint oil as masking agents, along with an encapsulated masking agent (sucralose). Psychophysical tests demonstrated that films which encapsulated both quinine and sucralose produced a significant and continuous sweet percept when compared to films without sucralose microspheres. Films with both quinine and sucralose microspheres also produced positive hedonic scores that did not differ from control films that contained only sucralose microspheres or only empty (blank) microspheres. The encapsulation of bitter taste stimuli in lipid microspheres, and embedding these microspheres in rapidly dissolving edible taste films that contain masking agents in both the film base and in microspheres, is a promising approach for diminishing the bitter taste of drugs and related compounds.